2020
DOI: 10.1177/0022146519899115
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Side Effects and Mental Health Paradoxes among Racial-Ethnic Minorities

Abstract: Sociologists have long struggled to explain the minority mental health paradox: that racial-ethnic minorities often report better mental health than non-Hispanic whites despite social environments that seem less conducive to well-being. Using data from the 2008–2013 Medical Expenditure Panel Survey (MEPS), this study provides a partial explanation for the paradox rooted in a very different disparity. Evidence from MEPS indicates that non-Hispanic whites consume more pharmaceuticals than racial-ethnic minoritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…Research on the minority mental health paradox indicates that blacks and Latinos report mental health outcomes that are equivalent to or more optimal than whites despite greater stress exposure (Louie and Wheaton 2019; Schnittker and Do 2020). However, evidence of this phenomenon is inconclusive in samples of adolescents and young adults, with several studies demonstrating higher levels of depressive symptoms among racial-ethnic minority groups (Adkins, Wang, and Elder 2009; Boardman and Alexander 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the minority mental health paradox indicates that blacks and Latinos report mental health outcomes that are equivalent to or more optimal than whites despite greater stress exposure (Louie and Wheaton 2019; Schnittker and Do 2020). However, evidence of this phenomenon is inconclusive in samples of adolescents and young adults, with several studies demonstrating higher levels of depressive symptoms among racial-ethnic minority groups (Adkins, Wang, and Elder 2009; Boardman and Alexander 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work suggests that the increase in overdose mortality is explained largely by the availability and relatively low cost of opioids rather than by economic conditions (123). Earlier increases in opioid deaths among non-Hispanic whites are also plausibly explained by a combination of greater access to prescription opioids, as well as racial bias in pain management (63,111,129).…”
Section: Opioidsmentioning
confidence: 99%
“…Previous studies have independently established the accuracy and reliability of Micromedex's coverage of the FDA’s black box warnings and drug–drug interactions (Barrons, 2004; Cheng, Guglielmo, Maselli, & Auerbach, 2010). In addition, a growing number of studies have used Micromedex to identify medication side effects and to assess the association between medication side effects and the health of the population (Do & Schnittker, 2020; Qato et al., 2018; Schnittker & Do 2020). This study identified 239 medications with insomnia side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate ordinary least squared and logistic models were used to assess the association between insomnia‐related outcomes and the use of medications with insomnia side effects. To address the issue of unobserved heterogeneity in health and other factors, all analyses controlled for the use of medications without insomnia side effects (Do & Schnittker, 2020; Qato et al., 2018; Schnittker & Do, 2020). If the relationship between medications with insomnia side effects and insomnia was driven by unobserved heterogeneity in health and other factors, the relationship between medications without known insomnia side effects and insomnia should be equally significant as that between medications with insomnia side effects and insomnia.…”
Section: Introductionmentioning
confidence: 99%